Anxious journeys : twenty-first-century travel writing in German - Baumgartner, Karin, 1964-; Shafi, Monika (Studies in German literature, linguistics, and culture., 2019)
The rich contemporary literature of travel has been the focus of numerous recent publications in English that seek to understand how travel narratives, with their distinctive representations of identities, places, and cultures, respond to today's globalized, high-speed world characterized by the dual mass movements of tourism and migration. Yet a corresponding cutting-edge discussion of twenty-first-century travel writing in German has until now been missing. The fourteen essays in Anxious Journeys redress this situation. They analyze texts by leading authors such as Felicitas Hoppe, Christoph Ransmayr, Julie Zeh, Navid Kermani, Judith Schalansky, Ilija Trojanow, and others, as well as topics such as Turkish-German travelogues and the relationship of comics to travel writing. The volume examines how writers engage with classic tropes of travel writing and how they react to the current sense of crisis and belatedness. It also links travel to ongoing debates about the role of the nation, mass migration, and the European project, as well as to Germany's place in the larger world order.